Contrasting mycorrhizal shifts underpin the recovery of soil microbial functions following forest restoration across climatic regions - Jiao Feng; Thomas W. Crowther; Yufei Lu; Zhongwen Liu; Shujie Zhao; Shu-Hai Wen; Qiaoyun Huang; Yu-Rong Liu (Forest Ecology and Management, 2026)

Epinephelus coioides lnc32039 promotes the infection of iridovirus SGIV via inhibiting immune response and apoptosis - Yin-Mei Lan; Wen-Feng Yang; Yu-Qin Ma; Yu-Rong Lei; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2026)

Multidimensional evaluation and quantification of tunnel shotcrete roughness using point cloud data - Yun-Jian Cheng; Rong-Feng Chen; Ming-Xing Ye; Wen-Ge Qiu; Feng Lu (Tunnelling and Underground Space Technology, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

Inhibition of methane production in an alpine wetland of the Tibetan plateau by carbon-based nanomaterials - Chengfang Ma; Rong Wen; Miao Lin; Hongfei Chi; Meiling Feng; Pengfei Liu (Environmental Research, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

From green revolution to multigene revolution: Breeding high-yield rice by design - Bo Zhang; Qingli Wen; Wenrui Feng; Rong Wang; Wenbo Liu; Wen Huang; Ahmed Khatab; Jiayang Li; Yongzhong Xing (Molecular Plant, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Experimental evidence on the bitumen role of the metal enrichment in the Erdaokan Ag-Pb-Zn deposit - Shun-Feng Yan; Xiao-Min Zheng; Lin Li; Hai-Yan Zheng; Mao-Wen Yuan; M. Santosh; Sheng-Rong Li (Organic Geochemistry, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Microglial Necroptosis Mediated by RIPK3 Leads to Retinal Ganglion Cell Apoptosis Through the Release of FGF2 After Ischemia/Reperfusion - Jian Liu; Anping Ma; Guangyi Huang; Wen Hu; Xin Xu; Rong Huang; Yaguang Hu; Qiaochu Cheng; Yanlin Feng; Dan Ye; Fan Xu; Aimin Sang (Journal of Molecular Neuroscience, 2025)

Spatial distribution and chemical characteristics of bastnäsite and monazite provide insights into the Bayan Obo deposit, the world's largest rare earth element mineralization - Jin Wang; Lin Li; M. Santosh; Guo-Ying Yan; Jun-Feng Shen; Mao-Wen Yuan; Masroor Alam; Zhao-Jing Wang; Sheng-Rong Li (Lithos, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Soil invertebrate diversity supports ecosystem multifunctionality along elevation gradients - Xiao-Min Zeng; Manuel Delgado-Baquerizo; Shuhai Wen; Jiao Feng; Wen Zhang; Qianggong Zhang; Yu-Rong Liu (Plant and Soil, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

Negative Impacts of Global Change Stressors Permeate Into Deep Soils - Shuhai Wen; Manuel Delgado‐Baquerizo; Tadeo Sáez‐Sandino; Jiaying Chen; Jiao Feng; Qiaoyun Huang; Emilio Guirado; Matthias C. Rillig; Yu‐Rong Liu (Ecology Letters, 2025)
Surface soils are highly vulnerable to multiple global change stressors associated with climate change and human activity; however, whether the impacts of this increasing number of stressors penetrate deeper soils remains virtually unknown. Here, we conducted a continental‐scale survey of soil profiles (0–100 cm). Results showed that multiple stressors jointly affect multiple soil functions (from soil carbon sequestration to pathogen control) across top (0–30 cm), subsurface (30–60 cm) and deep soils (60–100 cm). An increasing number of stressors was especially detrimental to the capacity of ecosystems to support productivity and regulate soil‐borne pathogens across all depths. Further analyses revealed that climatic stressors interact with multiple environmental stressors, diminishing multifunctionality across the soil profile. Our work demonstrates that the effects of multiple stressors can permeate the entire soil profile, highlighting that an increasing number of global change stressors at low levels significantly threaten multiple functions supported by deep soils.

Abnormal lipid metabolism and inflammatory response induced by aluminum led to the cognitive decline in mice - Rong Feng; Zhongyao Chen; Liang Chen; Wei Wei; Jiafeng Wen; Jingyu Zheng (NeuroToxicology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Energy level offsets determine the interplay between charge and energy transfer in all-small-molecule organic solar cells - Guanzhao Wen; Rong Hu; Junyi Feng; Jun Peng; Zhifeng Chen; Chengyun Zhang; Ningjiu Zhao; Xianshao Zou; Zhe Chen; Cuihong Liu; Wei Zhang (Chemical Engineering Journal, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Plastispheres as hotspots of microbially-driven methylmercury production in paddy soils - Yun-Yun Hao; Hui-Wen Liu; Jiating Zhao; Jiao Feng; Xiuli Hao; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Climatic seasonality challenges the stability of microbial‐driven deep soil carbon accumulation across China - Shuhai Wen; Jiaying Chen; Ziming Yang; Lei Deng; Jiao Feng; Wen Zhang; Xiao‐Min Zeng; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2023)
Microbial residues contribute to the long‐term stabilization of carbon in the entire soil profile, helping to regulate the climate of the planet; however, how sensitive these residues are to climatic seasonality remains virtually unknown, especially for deep soils across environmental gradients. Here, we investigated the changes of microbial residues along soil profiles (0–100 cm) from 44 typical ecosystems with a wide range of climates (~3100 km transects across China). Our results showed that microbial residues account for a larger portion of soil carbon in deeper (60–100 cm) vs. shallower (0–30 and 30–60 cm) soils. Moreover, we find that climate especially challenges the accumulation of microbial residues in deep soils, while soil properties and climate share their roles in controlling the residue accumulation in surface soils. Climatic seasonality, including positive correlations with summer precipitation and maximum monthly precipitation, as well as negative correlations with temperature annual range, are important factors explaining microbial residue accumulation in deep soils across China. In particular, summer precipitation is the key regulator of microbial‐driven carbon stability in deep soils, which has 37.2% of relative independent effects on deep‐soil microbial residue accumulation. Our work provides novel insights into the importance of climatic seasonality in driving the stabilization of microbial residues in deep soils, challenging the idea that deep soils as long‐term carbon reservoirs can buffer climate change.

Triterpene constituents from the fruits of Cyclocarya paliurus and their anti-HIV-1 IIIB activity - Wen-Chao Tu; Rong-Hua Luo; En Yuan; Kaunda-Joseph Sakah; Quan-Yu Yang; Wei-Lie Xiao; Yong-Tang Zheng; Mei-Feng Liu (Natural Product Research, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

Local temperature increases reduce soil microbial residues and carbon stocks - Xiao‐Min Zeng; Jiao Feng; Dai‐Lin Yu; Shu‐Hai Wen; Qianggong Zhang; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2022)
Warming is known to reduce soil carbon (C) stocks by promoting microbial respiration, which is associated with the decomposition of microbial residue carbon (MRC). However, the relative contribution of MRC to soil organic carbon (SOC) across temperature gradients is poorly understood. Here, we investigated the contribution of MRC to SOC along two independent elevation gradients of our model system (i.e., the Tibetan Plateau and Shennongjia Mountain in China). Our results showed that local temperature increases were negatively correlated with MRC and SOC. Further analyses revealed that rising temperature reduced SOC via decreasing MRC, which helps to explain future reductions in SOC under climate warming. Our findings demonstrate that climate warming has the potential to reduce C sequestration by increasing the decomposition of MRC, exacerbating the positive feedback between rising temperature and CO 2 efflux. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Together, our work suggests an important mechanism underlying long‐term soil C sequestration, which has important implications for the microbial‐mediated C process in the face of global climate change.

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Cooperation Search Algorithm for Power Generation Production Operation Optimization of Cascade Hydropower Reservoirs - Wen-jing Niu; Zhong-kai Feng; Yu-rong Li; Shuai Liu (Water Resources Management, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

A Eu(III)-based Metal Organic Framework: Selective Sensing of Picric Acid and Nursing Application Values On the Cerebral Edema Induced by Cerebral Hemorrhage Via Reducing the Coagulation Factor II Activity - Xiao-Chang Chen; Feng Xi; Rong Liu; Jia-Wen Zhou (Journal of Fluorescence, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Impact of calcium peroxide dosage on the control of nutrients release from sediment in the anoxic landscape water - Yi Wang; Wen-Huai Wang; Xin-Xin Lu; Lin-Lin Feng; Fu-Rong Xue; Lu-Qin Sun (Environmental Science and Pollution Research, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Changes by cadmium stress in lipid peroxidation and activities of lipoxygenase and antioxidant enzymes in Arabidopsis are associated with extracellular ATP - Qin-zheng Hou; Guang-ji Ye; Rong-fang Wang; Ling-yun Jia; Jun-yu Liang; Han-qing Feng; Jing Wen; Dai-long Shi; Qing-wen Wang (Biologia, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Normobaric Hyperoxia Extends Neuro- and Vaso-Protection of N-Acetylcysteine in Transient Focal Ischemia - Yushan Liu; Wen-Cao Liu; Yanyun Sun; Xianzhi Shen; Xiaona Wang; Hui Shu; Rong Pan; Chun-Feng Liu; Wenlan Liu; Ke Jian Liu; Xinchun Jin (Molecular Neurobiology, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

Bridge life cycle assessment with data uncertainty - Yu-Rong Zhang; Wen-Jie Wu; Yuan-Feng Wang (The International Journal of Life Cycle Assessment, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Hydrogen sulfide alleviates zinc toxicity by reducing zinc uptake and regulating genes expression of antioxidative enzymes and metallothioneins in roots of the cadmium/zinc hyperaccumulator Solanum nigrum L. - Xiang Liu; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Zhi-Jun Shen; Mei-Rong Luo; Gui-Feng Gao; Martin Simon; Kabir Ghoto; Hai-Lei Zheng (Plant and Soil, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Research and experimental testing of a new kind electrokinetic logging tool - Feng-Bo Li; Xiao-Dong Ju; Wen-Xiao Qiao; Jun-Qiang Lu; Bai-Rong Men (Applied Geophysics, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Functional analysis on immune deficiency (IMD) homolog gene in Chinese shrimp Fenneropenaeus chinensis - Ningning Feng; Dongdong Wang; Rong Wen; Fuhua Li (Molecular Biology Reports, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

Environmental Investigations and Molecular Typing of Aspergillus in a Chinese Hospital - Jun-hong Ao; Zhen-feng Hao; He Zhu; liang Wen; Rong-ya Yang (Mycopathologia, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Triterpenoid saponins from the root of Anemone tomentosa - Yi Wang; Wei Kang; Liang-jian Hong; Wen-li Hai; Xiao-yang Wang; Hai-feng Tang; Xiang-rong Tian (Journal of Natural Medicines, 2013)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Role of secretory protease inhibitor SPINK3 in mouse uterus during early pregnancy - Wen Chen; Bing-Chen Han; Rong-Chun Wang; Gao-Feng Xiong; Jing-Pian Peng (Cell and Tissue Research, 2010)

Solid-state fermentation of cornmeal with the ascomycete Morchella esculenta for degrading starch and upgrading nutritional value - Gui-Ping Zhang; Feng Zhang; Wen-Ming Ru; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2010)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Improving human micronutrient nutrition through biofortification in the soil–plant system: China as a case study - Xiao-E. Yang; Wen-Rong Chen; Ying Feng (Environmental Geochemistry and Health, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Effects of typical and atypical antipsychotics on glucose–insulin homeostasis and lipid metabolism in first-episode schizophrenia - Ren-Rong Wu; Jing-Ping Zhao; Zhe-Ning Liu; Jin-Guo Zhai; Xiao-Feng Guo; Wen-Bing Guo; Jing-Song Tang (Psychopharmacology, 2006)

Abnormal pollen development of bread wheat-Leymus mollis partial amphiploid - Xing-Feng Li; Shu-Bing Liu; Ju-Rong Gao; Wen-Hui Lu; Hong-Gang Wang (Euphytica, 2005)